Usage of Additive Manufacturing Techniques in Producing Orthotic Insole - Gandhi, Ankit; Vaishya, Dr. R.; Gupta, Anurag (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
Usage of 3 D printed objects has gained a huge interest in recent years. This has led to a variety of 3 D printed ready to use products in today’s market. In this review paper, the usage and testing of 3 D printed orthotic insoles has been discussed in detail. Thermoplastic Elastomers (TPE) and Thermoplastic polyurethane (TPU) are the most commonly used materials that are being used in customized printed orthotic insoles. Many 3D printers use these materials for the printing of customized orthotic insoles that are comfortable and assists the user in many foot disorders. After the product is produced it undergoes a series of testing for its mechanical and physical properties. A total of 13 research papers were identified and 7 were selected based on the abstract and the title. Based on the assessment of the total articles, 4 papers fulfilled predetermined qualitative criteria and were selected for a detailed review. Effects of many parameters have been studied that affected the properties of orthotic insoles but the main affecting factor was the infill density. Although there are many more parameters which could be studied and more better results can be provided.